An Integrated Diagnostic Approach to Severe Generalized Canine Tetanus: Serial Neurological, Clinicopathological and Electromyographic Assessment with Successful Clinical Management - Andrei Răzvan Codea; Amalia Marina Neagu; Ștefania-Mădălina Dandea; Helga Demény; Bogdan Florea; Yarden Lamy Casoy; Mihaela Niculae (Veterinary Sciences, 2026)
Tetanus is uncommon in dogs, which are considered relatively resistant to tetanospasmin, and detailed descriptions of the diagnostic evaluation of severe generalized cases remain limited. A 5.5-month-old intact male Miniature Schnauzer was presented four days after a puncture wound to the right pelvic limb. On admission the dog was alert but non-ambulatory, with generalized muscle rigidity, tremors, marked cervical hyperextension, hyperactive spinal reflexes, facial muscle spasms and dysphagia. Together with the wound history and rapid progression, these findings supported a presumptive diagnosis of generalized tetanus, clinically classified as Grade III. Serum collected before tetanus antitoxin administration contained no detectable antibodies against Clostridium tetani neurotoxin. Treatment comprised equine tetanus antitoxin, antimicrobials, multimodal sedation and muscle relaxation, enteral nutrition, intensive nursing and physiotherapy. Needle electromyography on day 10 showed increased insertional activity, positive sharp waves and fibrillation potentials, and continuous spontaneous motor unit activity. Despite patient young age and rapid disease progression, clinical improvement was evident from day 10, and the dog was discharged on day 16, ambulatory and eating voluntarily. This case highlights that severe generalized canine tetanus remains principally a clinical diagnosis, while serial neurological examination, clinicopathological monitoring and electromyography can strengthen diagnostic confidence, characterize disease progression and support clinical management.